Portrayal of the Exotic in Advertisements;The Indian Scenarios - K.P, Gayatridevi (International Journal of Psychosocial Rehabilitation, 2020)
Post colonialism and advertisements are two apparently disparate entities which could reveal the psychological and cultural imperialism that reigns the modern society, when one is analysed through the looking glass of the other.The modern societies often fail to realize the existing sovereignty of white superiority and continue to look at things from the perspectives of the coloniser. And this Eurocentric perspective has assumed normality in such a way that the descendants of the colonised have recognised themselves as the essential other. This could be further elaborated using the apparatus of advertisements in Indian society.The consciousness itself of the skin colour is not an inherently colonial way of thinking. But “fair is lovely” concept was injected into the psyche of the enslavedby the imperialists and the perpetual repression using this notion gradually converted it into an inseparable part of the innate value systems on which the identity itself is built. And the panacea was treating the Indianness in the politics of beauty, or the „desi‟ aspects of our lives as the exotic or the other and celebrating that as a progressive initiative towards finally accepting the roots of oneself. This paper intends to analyse this detour further in the lights of post colonialism, which was not entirely to a different tangent, rather falls right into the coloniser‟s stream of thought. One could argue that this adherence to the „superior‟ oppressor‟s philosophies is to obtain a vicarious pleasure of being the oppressor himself through identifying oneself with the coloniser‟s way of thinking.